Analysis of the SPW (School for Producing Entrepreneurs) Program and the Creative Product Subject to the Behavioral Business and Students Independence of XI Graders of Binakarya Mandiri, Bekasi - Ridhwan, Muh. Ardhi; Rivai Zainal, Veithzal; Hakim, Aziz (International Journal of Advanced Multidisciplinary, 2023)
This study aims to determine the impact of the SPW (School for Producing Entrepreneurs) Program and Creative product on the behavioral business and student independence of eleventh-grade students at Binakarya Mandiri, Bekasi, during the 2021–2022 academic year. This study was conducted at Binakarya Mandiri Vocational High School, Bekasi with a population comprising a portion of class XI, to determine the number of samples for each class utilizing cluster sampling data collection techniques to gather 59 students using the Taro Yamane formula. Entrepreneurial interest is the desire to generate business prospects without fear of the associated risks and a desire for entrepreneurial success. Using a pre- and posttest questionnaire, the researchers obtained research data. Prior to receiving support in the SPW program, Creative students' interest in entrepreneurship was assessed using a pretest questionnaire. In the meantime, the posttest questionnaire was used to determine the extent to which students were interested in entrepreneurship after obtaining aid from the entrepreneurial printing school program and the creative and entrepreneurship products field of study. This study employs quantitative descriptive data with a specific percentage utilizing the Azwar scale formula so that the percentage can be determined and results can be stated in words or phrases. According to the data analysis, the findings of the pretest questionnaire, with an average score of 61.90, fall into the moderate group, and the results of the posttest questionnaire, with a score of 79.55, go into the very high category. The results of hypothesis testing indicate that tcount 8.271 > ttable 2.081 at a significance level of 5% with n = 55 and that there is an influence of the entrepreneurial school program and the field of study of creative and entrepreneurial products on the business behavior and independence (interest in entrepreneurship) of students, with the magnitude of the effect being 56%, with the remainder influenced by internal and external factors.